Peran Orang Tua Dalam Membangun Karakter Beragama Pada Anak - Annisa Annisa; Noor Azida Batubara; Maya Pitriani; Muhammad Arsyad; Muttakin Muttakin; Yani Yani (JURNAL ILMIAH NUSANTARA, 2026)
In the era of globalization and rapid advances in information technology, the challenges of shaping children’s religious character have become increasingly complex. This study aims to investigate the role of parents as the primary educators in the development of children’s religious character. Using a qualitative approach, the research explores the experiences and perspectives of parents and children through semi-structured interviews. The findings indicate that parents can shape children’s religious character through various approaches, such as serving as positive role models, creating a supportive environment, and accompanying children in religious practices. Effective communication and positive reinforcement play an important role in the development of a strong personality in children. By involving children in religious activities and explaining moral values, their understanding and internalization of religious teachings can be strengthened. These findings are expected to provide new perspectives for parents and the wider community on the importance of religious character education in fostering a generation that not only understands but also practices religious values in everyday life.